1983
DOI: 10.3171/jns.1983.59.6.0945
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mannitol and furosemide on blood-brain osmotic gradient and intracranial pressure

Abstract: The effect of mannitol (1.0 gm/kg) and furosemide (0.7 mg/kg), alone and in combination, on the blood-brain extracellular fluid and cerebrospinal fluid (CSF) osmotic gradient, elevated intracranial pressure (ICP), CSF and serum osmolality, and urine output was studied in 26 mongrel dogs. Mannitol and furosemide, when used together, produced a greater (62.4% versus 56.6%) and more sustained (5 hours versus 2 hours) fall in ICP than mannitol alone. This correlated with a prolongation of the reversal of the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(39 citation statements)
references
References 29 publications
2
36
1
Order By: Relevance
“…In two studies in normal brain, no pressure gradients were found between CSF and the grey or white matter (Poll et al, 1972;Wiig and Reed, 1983). Reulen and collaborators (Reulen and Kreysch, 1973;Reulen et al, 1977) measured pressures in the normal brain and in a cold lesion model of the cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two studies in normal brain, no pressure gradients were found between CSF and the grey or white matter (Poll et al, 1972;Wiig and Reed, 1983). Reulen and collaborators (Reulen and Kreysch, 1973;Reulen et al, 1977) measured pressures in the normal brain and in a cold lesion model of the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In untreated patients with Received 19 February 1996 Revised 24 September 1996 Accepted 30 September 1996 Correspondence to: Y Boucher brain tumours, mean CSFP was found to vary between 24 and 33 mmHg (Kullberg and West, 1965;Miller and Leech, 1975;Alberti et al, 1978). The lower pressures in the cortex and tumour are probably not due to pressure differences between the ventricles and the parenchyma as, under normal conditions, CSFP and intraparenchymal IFP are similar (Poll et al, 1972;Wiig and Reed, 1983) and, in the case of brain lesions, intraparenchymal IFP is similar or higher than CSFP (Reulen and Kreysch, 1973;Reulen et al, 1977: Sundbarg et al, 1987. The low IFP in intracranial tumours at craniotomy is probably due to the management of patients with agents and procedures (e.g.…”
mentioning
confidence: 95%
“…Its effectiveness was demonstrated in several studies examining patients with head injury [7,8,9,10,11,12]. Pollay et al [13] also described a synergistic effect of mannitol and furosemide in reducing ICP, related to preferential excretion of water through the renal distal tubule which sustains the osmotic gradient, and potentially also to reduced CSF production. The relation of the occurrence of a rebound phenomenon to the osmotic agent used remains uncertain, as the few existing study results are conflicting [6, 14].…”
Section: Osmotherapymentioning
confidence: 96%
“…nih.gov/pubmed/, http://scholar.google.com.br/, and http://www.scielo.org/php/index.php) relative to the usage of omeprazole in clinical trials with naturally affected dogs with hydrocephalus. Clinical data on their use and effectiveness currently are lacking, although the use of omeprazole for the treatment of hydrocephalus and syringomyelia in dogs was already suggested within the veterinary literature (RUSBRIDGE; GREITZ;ISKANDAR, 2006;LAVELY, 2006;DEWEY, 2008;THOMAS, 2010), Medical treatment of hydrocephalus includes general supportive care and the administration of medications to restrict the production of CSF and hence reduce the ICP. Different medications has been traditionally used with this propose such as steroids (glucocorticoids), furosemid, manitol, and carbonic anhydrase blockers (acetazolamide) (SAHAR; TSIPSTEIN, 1978;POLLAY et al, 1983;BAGLEY, 2004;DEWEY, 2008;KIM et al, 2009;PARK et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data on their use and effectiveness currently are lacking, although the use of omeprazole for the treatment of hydrocephalus and syringomyelia in dogs was already suggested within the veterinary literature (RUSBRIDGE; GREITZ;ISKANDAR, 2006;LAVELY, 2006;DEWEY, 2008;THOMAS, 2010), Medical treatment of hydrocephalus includes general supportive care and the administration of medications to restrict the production of CSF and hence reduce the ICP. Different medications has been traditionally used with this propose such as steroids (glucocorticoids), furosemid, manitol, and carbonic anhydrase blockers (acetazolamide) (SAHAR; TSIPSTEIN, 1978;POLLAY et al, 1983;BAGLEY, 2004;DEWEY, 2008;KIM et al, 2009;PARK et al, 2009). Many of these drugs (furosemid, manitol, and carbonic anhydrase blockers) have diuretic activity, and caution must be exerted when using diuretic because electrolyte depletion is a common sequela; in addition, electrolyte loss is accelerated when diuretics are used in combination with steroids (glucocorticoids) (THOMAS, 2010).…”
Section: Introductionmentioning
confidence: 99%